Identifying persistent hot spot areas of undersized fish and crustaceans in southern european waters: implication for fishery management under the discard ban regulation - Milisenda, Giacomo (2021)
The recent establishment of the "landing obligation" under the reformed EU Common Fishery Policy has the twofold objective of reducing the excessive practice of discarding unwanted catch at sea and encouraging more selective and sustainable fisheries. Within this context, the awareness of the spatial distribution of potential unwanted catches is important for devising management measures aimed to decrease discards. This study analyzed the distribution of Hot Spot density areas of demersal fish and crustaceans below the Minimum Conservation Reference Size (MCRS) in four different southern European seas: continental Portuguese coast, Catalan Sea, South of Sicily, Liguria and northern Tyrrhenian Seas using both bottom trawl survey data and information on the spatial distribution of commercial fisheries. Critical areas for discarding were identified as zones where the highest densities of individuals below MCRS were consistently recorded throughout a series of years. Results clearly showed a patchy distribution of undersized individuals in each investigated area, highlighting the overlap between high density patches of both discards and fishing effort. The present findings provide a relevant knowledge for supporting the application of spatial-based management actions, such as the designation of Fisheries Restricted Areas (FRAs), in order to minimize the by-catch of undersized specimens and improve the sustainability of demersal fisheries